2008
DOI: 10.1590/s1415-47572008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between estrogen receptor and retinol-binding protein-4 polymorphisms as a tool for the selection of prolific pigs

Abstract: The aim of the present study was to investigate the association of the estrogen receptor (ER-PvuII) and retinolbinding protein 4 (RBP4-MspI) gene polymorphisms and their interactions with prolificacy in a commercial synthetic pig line reared in Brazil. A total of 10,374 piglet records from 218 sows and 817 litters were used for litter size analysis. Only females with three or four farrowings were included in the analysis. The mean litter size ranged from 5.0 to 19.5 piglets. DNA was extracted from leukocytes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Moreover, previous authors [ 1 , 9 ] concluded that the presence of B allele had a negative effect on the litter size, suggesting that A allele was in favor of prolificacy. In addition, Sun et al [ 21 ] reported that crossbreed pigs with the AA genotype produced 0.72 TNB, 0.64 NBA more than the BB genotypic sows, while Gonçalves et al [ 22 ] reported that A allele of RBP4 gene produced more piglets (TNB) and more live piglets per litter (NBA).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous authors [ 1 , 9 ] concluded that the presence of B allele had a negative effect on the litter size, suggesting that A allele was in favor of prolificacy. In addition, Sun et al [ 21 ] reported that crossbreed pigs with the AA genotype produced 0.72 TNB, 0.64 NBA more than the BB genotypic sows, while Gonçalves et al [ 22 ] reported that A allele of RBP4 gene produced more piglets (TNB) and more live piglets per litter (NBA).…”
Section: Discussionmentioning
confidence: 99%
“…The growing literature on relevant polymorphisms implicated in disease susceptibility may provide an alternative strategy for selection. For example, retinol-binding protein polymorphisms (Goncalves et al 2008) are associated with prolificacy in pigs, but effects on tissue concentrations are unknown.…”
Section: Geneticsmentioning
confidence: 99%
“…For example, retinol-binding protein polymorphisms (Goncalves et al . 2008) are associated with prolificacy in pigs, but effects on tissue concentrations are unknown.…”
Section: Geneticsmentioning
confidence: 99%
“…Besides, a possible dependence on the genetic background should be taken into account, because epistatic effects could be affecting pig prolificacy as recently reported [ 38 , 39 ]. Gonçalves et al [ 14 ] have pointed out that effects of the RBP4-MspI polymorphism on litter size depend on the genotype of the ESR1 - Pvu II allele in a comparison between sows from three genotypic classes. The litter size for second and later parities of sows carrying either ESR1 allele A/ RBP4 genotype 11 or ESR1 allele B/ RBP4 genotype 22 was greater than that of sows grouped in the third class ( ESR1 AA/ RBP4 22 and ESR1 BB/ RBP4 11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gonçalves et al . [ 14 ] have performed an interesting study in a commercial population that revealed a significant interaction on litter size between RBP4 - Msp I and ESR1-PvuII polymorphisms.…”
Section: Introductionmentioning
confidence: 99%